Evaluate the Advanced Machining on Metal Matrix Composite Manufactured Via Adding Nano-Aluminum Oxide on Recycled Aluminum Waste - S.H.A. Alfatlawi; N.M. Khabou; W.A. Mughir (Archives of Metallurgy and Materials)
A waste of electrical power cables becomes a major problem at the present time, so they must be disposed in order to preserve the environment, and to obtain a raw material for the industry with low cost. In this work, recycled materials is prepared by heating up the aluminum wires up to 650°C for melting to prepare the aluminum alloy as a matrix. Then, the matrix reinforced by the nanoparticles (30 nm) of aluminum oxide (Al2O3) to prepare the composite using the stir casting technique. The electrical discharge machining (EDM) as advanced machining, is used to evaluate the materials behavior through the operation. Taguchi method is used to design and determine the suitable input and output factors. The scanning electron microscope (SEM) and hardness are tested before and after machining. The results appeared that improving in microstructure, also the hardness of the composite improved (37.2% and 22.6%) before and after machining.